Friendship matters: a research agenda for aphasia. Issue 3 (4th March 2022) - Azios, Jamie H.; Strong, Katie A.; Archer, Brent; Douglas, Natalie F.; Simmons-Mackie, Nina; Worrall, Linda
ABSTRACT: Background : Social isolation and loneliness are often present after aphasia and lead to negative health, social, and physical outcomes. Maintaining social connections after aphasia has been identified as an important target for intervention, but is not regularly addressed in aphasia intervention. While many persons with aphasia maintain relationships with immediate family members after brain injury, there are considerable changes to the substance and quantity of friendship networks early on in the recovery period. Aims : The aims of this article are to examine the literature on the topic of friendship within and across disciplines and to propose a research agenda for supporting the maintenance of friendships in persons living with aphasia. Main Contribution : The benefits of friendship to quality of life and wellbeing are well documented. Persons living with aphasia are at high risk for social isolation and reduction of friendship network due to multiple factors including reduced language capacity and social participation, costs and benefits associated with sustaining friendships, and changing social roles and identities. This article identifies 1) prospective research variables that may influence the creation, maintenance, and dissolution of friendship networks, 2) requirements of friendship research based upon these variables, 3) descriptions of interventions designed to improve existing and new friendships, and 4) potential outcome measures for capturing friendship changes and general well-being. We also highlight the link between reducing social isolation and loneliness by targeting friendship at an early stage in the recovery process and recommend a detailed plan for preventing the loss of friendship networks for people with aphasia. Conclusions : Strategic research and development of interventions targeting the maintenance of existing friendships is necessary to support the reduction of social isolation in persons with aphasia. The authors propose a research agenda which includes co-design of research projects and interventions for friendship maintenance as one means of addressing the issue of social isolation in persons with aphasia.